OpenStack Trove - Kumar, Amrith; Shelley, Douglas (Expert's voice in open source., 2015)
OpenStack Trove is your step-by-step guide to set up and run a secure and scalable cloud Database as a Service (DBaaS) solution. The book shows you how to set up and configure the Trove DBaaS framework, use prepackaged or custom database implementations, and provision and operate a variety of databasesĐÁìncluding MySQL, PostgreSQL, MongoDB, Cassandra, and RedisĐÁìn development and production environments. Authors Amrith Kumar and Douglas Shelley, both active technical contributors to the Trove project, describe common deployment scenarios such as single-node database instances and walk you through the setup, configuration, and ongoing management of complex database topics like replication, clustering, and high availability. The book provides detailed descriptions of how Trove works and gives you an in-depth understanding of its architecture. It also shows you how to avoid common errors and debug and troubleshoot Trove installations, and perform common tasks such as.